Pendidikan Agama Islam sebagai Pilar Kehidupan Beretika Siswa di Madrasah Aliyah Jabal Noer Sidoarjo - Arifin, Nurul; Masnawati, Eli (TSAQOFAH, 2024)
This research is motivated by Islamic Religious Education as a Pillar of Students' Ethical Life. Therefore, research at MA Jabal Noer is a curative solution for the current generation and preventive for future generations. This article is the result of field research using qualitative research methods. Data collection was carried out through observation, interviews and documentation. Then the data results were analyzed using descriptive research. The results of the research show that the formation of Islamic religious education values in students at MA Jabal Noer Throughout Sidoarjo has begun to appear, is developing well and has begun to be implemented in everyday life. The factors that influence continuity during the activity process are oneself, teachers, family and the environment. The internal supporting factors include the many parties who support the continuity of activities, the availability of supporting facilities and infrastructure, the high level of enthusiasm of students. Meanwhile, externally, namely competent trainers, extensive organizational relationships and various events/competitions at various levels. Internally, the constraints found were the low interest of students in taking part in extra qiro'ah and the busyness of trainers, while from an external perspective, namely parental permission.